Development of coaching learning techniques to overcome language errors of elementary students - Kartolo, Rahmat; Sutikno, Sutikno; Saputra, Sischa Sri Ar; Asnawi, Asnawi; Sutarini, Sutarini (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
This research investigates the systematic development and implementation of coaching-based learning techniques aimed at addressing common language errors among elementary students. Utilizing a Research and Development (R&D) methodology with the ADDIE model framework, this study demonstrates how coaching approaches can transform traditional error correction practices into student-centered learning opportunities. The research findings reveal significant reductions in grammatical, lexical, and phonological errors among participating students, with notable improvements in confidence and self-regulation skills. The coaching techniques developed through this structured process show particular effectiveness in fostering student autonomy and metacognitive awareness, enabling elementary learners to identify and address their own language errors more effectively than traditional correction methods. These findings contribute to the growing body of evidence supporting coaching-based pedagogies in elementary language education.